Quercetin Alleviates Diabetic Peripheral Neuropathy by Regulating Axon Guidance Factors and Inhibiting the Rho/ROCK Pathway in vivo and in vitro - Song W; Li Y; Jia Y; Xu L; Kang L; Yang Y; Wang S; Zhang Q; Wu Q (Diabetes, Metabolic Syndrome and Obesity)
Wei Song,1,2,* Yaoyang Li,1,* Yifan Jia,1 Lingling Xu,3 Lin Kang,4 Yunshuang Yang,5 Shuyu Wang,1 Qian Zhang,1 Qunli Wu1 1Department of Traditional Chinese Medicine, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of China; 2Institute of Clinical Medicine, National Infrastructures for Translational Medicine, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of China; 3Department of Endocrinology, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of China; 4Department of Geriatric, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of China; 5Department of Preventive Medicine, Beijing Longfu Hospital, Beijing, 100010, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qian Zhang; Qunli Wu, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People’s Republic of China, Email zhangqian1@pumch.cn; chinlie@163.comPurpose: The axon guidance factors and Rho/ROCK pathway play crucial roles in axon protection and nerve repair and has been implicated in the development of diabetic peripheral neuropathy (DPN). This study investigates the protective effects of quercetin against DPN, focusing on axon guidance factors and Rho/ROCK pathway.Methods: DPN was induced by intraperitoneal injection of streptozotocin (STZ) to Sprague-Dawley rats. The DPN model rats were allocated into three groups and administered quercetin at two different doses (30 mg/kg/day and 60 mg/kg/day) or a placebo. Concurrently, healthy rats were divided into two groups and administered either a placebo or quercetin (60 mg/kg/day). Administration was initiated 8 weeks post-STZ injection and continued for a duration of six weeks. To assess quercetin’s neuroprotective effects, biochemical analyses, neurological function tests (mechanical threshold, thermal response latency, motor nerve conduction velocity), and morphological assessments via transmission electron microscopy were conducted. Immunofluorescence and immunohistochemical assays were performed on sciatic nerve tissue and high glucose-induced RSC96 rat Schwann cells to explore quercetin’s pharmacological effects on DPN.Results: Quercetin exhibited neuroprotective effects on both DPN rats and RSC96 cells exposed to high-glucose. A six-week administration of quercetin at both doses significantly improved the peripheral neurological functions and alleviated the pathological changes in sciatic nerve of DPN rats (P< 0.05). Mechanistically, quercetin markedly upregulated the expressions of axonal growth factors, Slit-2 and Netrin-1 in vivo and in vitro (P< 0.05), while inhibiting the aberrant activation of Rho/ROCK signaling pathway in the sciatic nerve of DPN rats.Conclusion: Our findings suggest that quercetin improves DPN through a novel mechanism, indicating its potential as a therapeutic agent for DPN therapy. Keywords: quercetin, diabetic peripheral neuropathy, Rho/ROCK pathway, axon guidance factor, Netrin-1, Slit-2